2020
DOI: 10.1155/2020/8898370
|View full text |Cite
|
Sign up to set email alerts
|

Acorn Oil: Chemistry and Functionality

Abstract: Acorn oil has been receiving increasing attention due to its nutritional potentials. However, its application as a novel food ingredient has not yet been fully explored. This paper summarizes chemical composition, extraction methods, potential health benefits, and current applications of acorn oil, with the aim of providing suggestions for its exploitation. Acorn oil is an excellent source of essential fatty acids (oleic, linoleic, α-linolenic, and palmitic acids). Acorns are a rich source of tocopherols, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 57 publications
0
21
0
7
Order By: Relevance
“…Starch is a mixture of two biopolymers: amylose and amylopectin. e two polysaccharides are homoglycans with only two types of chain linkages, α- (1)(2)(3)(4) bonds of the main chain and α- (1)(2)(3)(4)(5)(6) bonds in the branching points. e resulting starch showed a wide variation in the chemical composition (Table 1).…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch is a mixture of two biopolymers: amylose and amylopectin. e two polysaccharides are homoglycans with only two types of chain linkages, α- (1)(2)(3)(4) bonds of the main chain and α- (1)(2)(3)(4)(5)(6) bonds in the branching points. e resulting starch showed a wide variation in the chemical composition (Table 1).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…ese species produce a widely known fruit, commonly identified as acorns, which are of vital importance for both humans and animals. Acorns are a good source of starch, protein, fat, minerals (such as P, K, Ca, and Mg), unsaturated fatty acids (i.e., oleic acid), and vitamins (mostly A and E) [2][3][4][5][6][7][8]. In addition, acorns contain numerous biologically active compounds (such as tannins, phenolic acids, and flavonoids), which are essential in the human diet to maintain an adequate level of antioxidants [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high amount of oleic and linoleic fatty acids, this high ratio was in accordance with previous results reported for the Quercus species. 19 The predominance of USFA confer QSAR and QSAS oils some important medicinal activity such as decreasing the plasma concentration of total and LDL cholesterol, enhancing metabolic and cardiovascular events, 42 and may as well help reduce the risk of developing some diseases like rheumatoid arthritis or asthma, diabetes, and perhaps even cancer. 43 Tocopherols Tocopherols are known as natural antioxidants.…”
Section: Organoleptic and Physicochemical Characteristicsmentioning
confidence: 99%
“…6 The oil is also used in cosmetic preparations and combined with other ingredients like avocado oil and beeswax to treat skin irritation and eczema. 19 Studies have shown that acorns oil possess similar nutritional quality and physicochemical properties as olive oil. 10,19,20,21 Quercus suber L. is one of the principal extending oak tree species in the western Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation